2016
DOI: 10.1155/2016/7028289
|View full text |Cite
|
Sign up to set email alerts
|

Nanog Predicts Poor Prognosis in Human Pancreatic Cancer and Is Downregulated by QingyihuaJi Formula in Pancreatic Cancer Stem Cells

Abstract: Qingyihuaji formula (QYHJ), confirmed efficacious in a series of clinical trials, has been applied to human pancreatic carcinoma treatment in Shanghai Cancer Center for years. Recent evidence highlighted that pluripotent stem cells transcription factor Nanog plays a pivotal role in carcinogenesis. However, there is little published information regarding the underlying clinical significance and mechanisms of transcription factor Nanog in pancreatic cancer. In this study, our results indicated that Nanog is over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Four studies evaluated non-small cell lung cancer (NSCLC), 5 , 32 34 four evaluated gastric cancer (GC), 9 , 26 , 27 , 38 and five evaluated OSCC; 8 , 15 , 28 , 29 , 36 breast cancer, 6 , 30 , 31 hepatocellular carcinoma (HCC), 7 , 25 , 39 and ovarian cancer (OC) 13 , 21 , 22 were each evaluated in three studies. Esophageal squamous cell carcinoma (ESCC), 10 , 23 colorectal cancer (CRC), 11 , 16 and pancreatic cancer (PC) 12 , 24 were each evaluated in two studies. Nasopharyngeal carcinoma (NPC), 14 astrocytoma, 20 cervical cancer (CC), 37 tongue squamous cell carcinoma (TSCC), 35 and mucoepidermoid carcinoma (MEC) 19 were each evaluated in one study.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated non-small cell lung cancer (NSCLC), 5 , 32 34 four evaluated gastric cancer (GC), 9 , 26 , 27 , 38 and five evaluated OSCC; 8 , 15 , 28 , 29 , 36 breast cancer, 6 , 30 , 31 hepatocellular carcinoma (HCC), 7 , 25 , 39 and ovarian cancer (OC) 13 , 21 , 22 were each evaluated in three studies. Esophageal squamous cell carcinoma (ESCC), 10 , 23 colorectal cancer (CRC), 11 , 16 and pancreatic cancer (PC) 12 , 24 were each evaluated in two studies. Nasopharyngeal carcinoma (NPC), 14 astrocytoma, 20 cervical cancer (CC), 37 tongue squamous cell carcinoma (TSCC), 35 and mucoepidermoid carcinoma (MEC) 19 were each evaluated in one study.…”
Section: Resultsmentioning
confidence: 99%
“…NANOG protein was expressed in 81% of cancer tissue; expression was strong in 26%, moderate in 32%, weak in 23% and it was absent in 19% of samples. 60 NANOG might thus be associated with the early stages of pancreatic cancer and might be used as a potential prognostic marker. 58,59…”
Section: Nanog In Cancermentioning
confidence: 99%
“…It consists of four exons and three introns, and encodes 305 amino acids. It is the key genes for stem cells on maintain self-proliferation and multidirectional differentiation [34–36]. With the development of research, NANOG has been found highly expression in breast cancer, spermatogonioma, gastric cancer, intestinal cancer, cervical cancer, oral squamous cell cancer and pancreatic cancer, and so on.…”
Section: Discussionmentioning
confidence: 99%